2023
DOI: 10.1108/ijshe-11-2022-0369
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sustainability education on students’ entrepreneurial intentions

Hasnan Baber,
Mina Fanea-Ivanovici,
Paul Sarango-Lalangui

Abstract: Purpose This study aims to examine the influence of sustainability education in 15 Indian universities and the mediating role of the theory of planned behavior in predicting students’ intentions to start an enterprise supporting sustainability. Design/methodology/approach The data, which consists of 422 samples, was collected from 15 universities in India. It was analyzed through partial least squares structural equation modeling, which is frequently used for prediction models. The model was further checked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…However, some studies, such as that of Hechavarria et al [29], did not find a significant impact of education on the likelihood of achieving environmental objectives. Numerous other studies have also demonstrated the existence of a positive impact of education on a company's focus on sustainable business [97][98][99]. Consequently, we propose the following hypotheses:…”
Section: Demographic Factorsmentioning
confidence: 83%
See 2 more Smart Citations
“…However, some studies, such as that of Hechavarria et al [29], did not find a significant impact of education on the likelihood of achieving environmental objectives. Numerous other studies have also demonstrated the existence of a positive impact of education on a company's focus on sustainable business [97][98][99]. Consequently, we propose the following hypotheses:…”
Section: Demographic Factorsmentioning
confidence: 83%
“…Similar trends have been observed for social goals. It has been found that women, in general, are more inclined towards sustainable business practices than men [98,99]. Furthermore, it has been found that businesses led by women exhibit more a positive link between sustainability entrepreneurship and overall business success [28].…”
Section: Demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation